In vitro wear resistance of three types of polymethyl methacrylate denture teeth - Katia Rodrigues Reis; Gerson Bonfante; Luiz Fernando Pegoraro; Paulo Cesar Rodrigues Conti; Pedro Cesar Garcia de Oliveira; Osvaldo Bazzan Kaizer (University of São Paulo, 2008)
The wear resistance of denture teeth is important to the longevity of removable prostheses of edentulous patients. The ability of denture teeth to maintain a stable occlusal relationship over time may be influenced by this property. The purpose of this in vitro study was to evaluate the wear resistance of polymethyl methacrylate (PMMA) denture teeth based on their chemical composition when opposed by a ceramic antagonist. The maxillary canines (n=10) of 3 PMMA denture teeth (Trubyte Biotone, cross-linked PMMA; Trilux, highly cross-linked IPN (interpenetrating polymer network)-PMMA; and Vivodent, highly cross-linked PMMA) were secured in an in vitro 2-body wear-testing apparatus that produced sliding contact of the specimens (4.5 cycles/s, sliding distance of 20 mm, under 37°C running water) against glazed or airborne particle abraded ceramic. Wear resistance was measured as height loss (mm) under 300 g (sliding force) after 100,000 cycles, using a digital measuring microscope. Mean values were analyzed by 2-way ANOVA and Tukey's test (a=0.05). The wear of Trubyte Biotone (0.93 ± 0.14 mm) was significantly higher than that of both other types of teeth tested against abraded ceramic (p<0.05). The Vivodent tooth (0.64 ± 0.17 mm) exhibited the best wear resistance among the denture teeth tested against airborne particle abraded ceramic. There were no statistically significant differences (p>0.05) in wear among the 3 denture teeth evaluated against glazed ceramic. Trilux and Vivodent teeth tested against either glazed or airborne particle abraded ceramic did not differ significantly from each other (p<0.05). All teeth showed significantly more wear against airborne particle abraded ceramic than against glazed ceramic (p<0.05). In conclusion, the three types of PMMA denture teeth presented significantly different wear resistance against the abraded ceramic. The high-strength PMMA denture teeth were more wear-resistant than the conventional PMMA denture tooth.